A manual for writers of research papers, theses, and dissertations : Chicago Style for students and researchers - Turabian, Kate L.; Booth, Wayne C.; Colomb, Gregory G.; Williams, Joseph M.; Bizup, Joseph, 1966-; FitzGerald, William T. (Chicago ; London : The University of Chicago Press, 2018)
"This new edition of the classic reference work on writing research papers recognizes recent developments in information literacy--including finding, evaluating, and citing a wide range of digital sources--and the evolving use of software for citation management, graphics, and paper format and submission while continuing to reflect best practices for research and writing, as adapted from the most recent editions of The Craft of Research and The Chicago Manual of Style."--Provided by publisher.
Includes bibliographical references (pages 421-446) and index.
Keywords: Dissertations, Academic -- Handbooks, manuals, etc; Academic writing -- Handbooks, manuals, etc